Analysis of The Impact of Handwashing with Soap Policy on Water Quality in Public Facilities: A Case Study in Palangka Raya, Indonesia - Achmad Imam Santoso; Azhari, Muh.; Putro, Dhymas Sulistyono (Indonesian Journal of Chemical Studies, 2023)
Coronavirus disease 2019 (Covid-19) has changed lifestyles. One of the new habits practiced by the community is washing hands. The government had issued a policy stipulated in the decree of the Minister of Health of the Republic of Indonesia number HK.01.07/Menkes/382/2020 concerning Health Protocols for Communities in Public Places and Facilities in the Context of Prevention and Control of Covid-19. Washing hands with soap is an effective step to break the chain of transmission of Covid-19. This research obtained samples of handwashing disposal and surface water at three public facilities in Palangka Raya city, i.e. G. Obos XX market, Pasar Besar, and KPD Supermarket that examined for the parameter of BOD, COD, TSS, and detergent content in the area. The result was the handwashing disposal and the surface water of three public facilities had BOD, COD, TSS, and detergent levels exceeding the surface water quality standard. Disposal of handwashing with soap waste directly into surface water causes a decrease in surface water quality